Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.1947
|View full text |Cite
|
Sign up to set email alerts
|

SAT0200 Long term safety of filgotinib in the treatment of rheumatoid arthritis: week 108 data from a phase 2b open-label extension study

Abstract: Background:Filgotinib (FIL) is an orally administered, selective inhibitor of Janus Kinase 1 (JAK1) in Phase 3 development for the treatment of rheumatoid arthritis (RA).Objectives:Assess the long-term safety and efficacy of FIL in the DARWIN 3 open-label extension study.Methods:Two 24-week Phase 2b studies were completed in patients (pts) with moderately to severely active RA (DARWIN 1, DARWIN 2; Ref 1, 2). Following study completion, pts were offered FIL in the ongoing DARWIN 3 extension study: 100 mg QD (US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Based on the results of both studies, filgotinib as a single therapy or combined with MTX is an effective benefit in improving PROs, functional state and quality of life in RA subjects with high disease activity (Genovese, Westhovens, et al, 2016, 2018). The DARWIN 3 study in subjects with RA investigates the long‐term safety and effectiveness of filgotinib in these participants (Westhovens et al, 2018). In this study, filgotinib showed adequate safety and durable efficacy profile (Westhovens et al, 2018).…”
Section: Clinical Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of both studies, filgotinib as a single therapy or combined with MTX is an effective benefit in improving PROs, functional state and quality of life in RA subjects with high disease activity (Genovese, Westhovens, et al, 2016, 2018). The DARWIN 3 study in subjects with RA investigates the long‐term safety and effectiveness of filgotinib in these participants (Westhovens et al, 2018). In this study, filgotinib showed adequate safety and durable efficacy profile (Westhovens et al, 2018).…”
Section: Clinical Developmentsmentioning
confidence: 99%
“…The DARWIN 3 study in subjects with RA investigates the long‐term safety and effectiveness of filgotinib in these participants (Westhovens et al, 2018). In this study, filgotinib showed adequate safety and durable efficacy profile (Westhovens et al, 2018).…”
Section: Clinical Developmentsmentioning
confidence: 99%